Enhanced fluorescence properties of carbon dots in polymer films. Issue 29 (29th June 2016) - Liu, Yamin; Wang, Ping; Shiral Fernando, K. A.; LeCroy, Gregory E.; Maimaiti, Halidan; Harruff-Miller, Barbara A.; Lewis, William K.; Bunker, Christopher E.; Hou, Zhi-Ling; Sun, Ya-Ping
Abstract : Fluorescence intensities of carbon dots are substantially enhanced in the confined environment in polymeric films. Abstract : Carbon dots of small carbon nanoparticles surface-functionalized with 2, 2′-(ethylenedioxy)bis(ethylamine) (EDA) were synthesized, and the as-synthesized sample was separated on an aqueous gel column to obtain fractions of the EDA–carbon dots with different fluorescence quantum yields. As already discussed in the literature, the variations in fluorescence performance among the fractions were attributed to the different levels and/or effectiveness of the surface functionalization–passivation in the carbon dots. These fractions, as well as carbon nanoparticles without any deliberate surface functionalization, were dispersed into poly(vinyl alcohol) (PVA) for composite films. In the PVA film matrix, the carbon dots and nanoparticles exhibited much enhanced fluorescence emissions in comparison with their corresponding aqueous solutions. The increased fluorescence quantum yields in the films were determined quantitatively by using a specifically designed and constructed film sample holder in the emission spectrometer. The observed fluorescence decays of the EDA–carbon dots in the films and in the solution were essentially the same, suggesting that the significant enhancement in fluorescence quantum yields from the solution to films is static in nature. Mechanistic implications of the results, including a rationalization in terms of the compression effect on the surface passivation layer (similar to a soft corona) in carbon dots when embedded in the more restrictive film environment resulting in more favorable radiative recombinations of the carbon particle surface-trapped electrons and holes, and also potential technological applications of the brightly fluorescent composite films are highlighted and discussed.